Multidisciplinary management of spinal aneurysmal bone cysts: A single-center experience. Issue 5 (October 2019) - Desai, Sudhen B; O'Brien, Cormac; Shaikh, Raja; Hedequist, Daniel; Proctor, Mark; Orbach, Darren B; Padua, Horacio
Objective: The management of spinal aneurysmal bone cysts (ABCs) is complex and often requires multimodality therapy, including surgical intervention to stabilize the axial skeleton, and avoid neurologic injury or death. With en bloc resection, ABCs have a recurrence rate of 12%, which increases to >50% with subtotal resection. The use of doxycycline sclerotherapy has been reported to reduce the recurrence rate of non-spinal ABCs to 5% at >24 month follow-up. We retrospectively reviewed our institutional results for sodium tetradecyl sulfate (STS)/doxycycline sclerotherapy and surgical intervention for spinal ABCs, to assess our treatment paradigm for these tumors and inform our future approach to these lesions. Methods: Three cervical, two thoracic and two lumbar spine ABCs were treated in seven patients with spine-exclusive disease at our institution from 2011 to the present. The most common presenting complaint was pain. Each patient was retrospectively reviewed for clinical symptomology, number of treatments, technique and clinical follow-up. Qualitative assessment of improvement was based on the most recent clinical evaluation. Results: The cohort underwent a mean of three treatment sessions (range 2–15). All were treated with STS and/or doxycycline. Five patients underwent surgical intervention at some point, either before or following sclerotherapy. After the last sclerotherapy session, four patients reported stable or improved pain symptoms, while two reported progressive pain that required surgical intervention for that indication. One patient, who underwent both multiple rounds of sclerotherapy and surgical resection, died due to acute on chronic cervical spine collapse with cord compression and inability to control disease. Conclusion: We report our experience in the treatment of spinal column ABCs. Stabilization or improvement in pain was seen in four patients, while the remainder had progressive disease. Our multidisciplinary approach allows patients to receive the most appropriate treatment at presentation and thereafter, for symptom amelioration or spinal stability. Important future goals are to quantitatively assess changes in symptoms over time and to incorporate a reproducible radiographic endpoint for the assessment of treatment efficacy.